How Resilient Were Emerging Economies to the Global Crisis? - Didier, Tatiana (2012)
This paper studies the cross-country incidence of the 2008-2009 global crisis and documents a structural break in the way emerging economies responded to the global shock. Contrary to popular perceptions, emerging market economies suffered growth collapses comparable, or even larger, to those experienced by advanced economies during the crisis. With such large financial and real shock, most of the world economy came to a halt when the crisis hit, with most countries resuming their pre-crisis growth rates afterwards. While emerging economies were not able to avoid the crisis collapse, they grew at a higher rate during the post crisis, relative to before and, as usual, to advanced countries. Moreover, emerging economies initiated their recovery sooner. Breaking with the past, emerging economies were able to conduct countercyclical policies, and became more similar to developed countries in softening the impact of the crisis and in their ability to pursue expansionary policies.